Left ventricular remodeling: is there a real impact of cardiac rehabilitation?. (11th May 2021) - Cunha, NPD; Aguiar-Ricardo, I; Rodrigues, T; Silverio Antonio, P; Couto Pereira, S; Alves Da Silva, P; Valente Silva, B; Brito, J; Pinto, R; Lemos Pires, M; Borges, M; Jordao, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: A number of randomized controlled trials have examined the effect of exercise training on left ventricle (LV) remodeling in individuals with cardiovascular disease. However, the results of these trials have been inconclusive.  Purpose: Evaluation of the impact of a cardiac rehabilitation program (CRP) on left ventricle remodelling evaluated by echocardiogram.  Methods: Observational single centre study including consecutive patients, undergoing structured CRP since June 2016 until February 2020. Phase II CRP included 3 months of exercise training, aerobic and strength exercise, individually prescribed, 3 times a week, 60 minutes sessions. All patients were submitted to a clinical evaluation, echocardiogram, and cardiopulmonary exercise test before and after the CRP. Results: 205 patients (62.6 ± 11 years, 83.4% men, 82.3% ischemic disease) were included in a phase II CRP. Most patients had ischemic disease (82.3%) and 23.5% of patients had left ventricular ejection fraction (LVEF) <40%. Of the cardiovascular risk factors, hypertension was the most prevalent (76%), followed by dyslipidaemia (67.4%), active smoking (45.9%) and diabetes (26.9%).  After the CRP, there was a significant improvement of LVEF (from 48.3 ± 13 to 52 ± 11.6 %, p = 0.001) and a significant reduction of LV volumes (LV end-diastolic volume, LVEDV, decreased from 140 ± 81 to 121 ± 57, p = 0.002; LV end-systolic volume, LVESV, reduced from 80 ± 75 to 64 ± 48, p = 0.004). Considering only the patients with LVEF < 40% (n = 38), the improvement was even greater: LVEF increased from 30 ± 8 to 39 ± 13 (p = 0.002); LVEDV reduced from 206 ± 107 to 159 ± 81 (p = 0.001) and LVESV reduced from 142 ± 99 to 101 ± 66 (p = 0.002). 63.6%(n = 14) of these patients improved at least 10% of LVEF and only 1 of them had a cardiac resynchronization therapy device.  Conclusions: A phase II CR program was associated with significant improvements in left ventricular reverse remodelling irrespective of baseline EF classification. Those with reduced baseline EF derived an even greater improvement, highlighting the great importance of CR in this subgroup of patients.